ORGANIZATIONAL AND ECONOMIC MECHANISMS FOR COMMERCIALIZATION OF GREEN TECHNOLOGIES IN KAZAKHSTAN (Journal of Economic Research & Business Administration, 2019)
Green technologies are essential tools to ensure sustainable development of the economy. The transition to a green economy requires changes in existing governance approaches, institutions, and markets. In this regard, authors analyzed the current state and implementation of green technology projects in Kazakhstan. Barriers identified through extensive literature review and semi-structured expert interviews were validated through discussions with with experts and twenty-one barriers have been categorized into six dimensions. They were placed on sheet by levels of authority to solve the problem and periods for changing the situation. Understanding various barriers leads to important lessons in designing policy instruments and institutions for diffusing green technologies. Research goal is to develop organizational and economic mechanisms for commercialization of green technologies in Kazakhstan. During the study, authors used comprehensive literature review, expert interviews, analysis and synthesis methods, and integral approach to elaborate mechanisms’ framework. As a result, objects and subjects, basic principles, appropriate organizational and economic instruments, tools, four goals and eleven objectives were proposed. The proposed framework permits managers and practitioners to make decisions in the most effective way.